Lactulose and Melibiose Inhibit α-Synuclein Aggregation and Up-Regulate Autophagy to Reduce Neuronal Vulnerability - Chen, Chiung Mei (Cells, 2020)
Parkinson’s disease (PD) is a neurodegenerative disease characterized by selective dopaminergic (DAergic) neuronal degeneration in the substantia nigra (SN) and proteinaceous α-synuclein-positive Lewy bodies and Lewy neuritis. As a chemical chaperone to promote protein stability and an autophagy inducer to clear aggregate-prone proteins, a disaccharide trehalose has been reported to alleviate neurodegeneration in PD cells and mouse models. Its trehalase-indigestible analogs, lactulose and melibiose, also demonstrated potentials to reduce abnormal protein aggregation in spinocerebellar ataxia cell models. In this study, we showed the potential of lactulose and melibiose to inhibit α-synuclein aggregation using biochemical thioflavin T fluorescence, cryogenic transmission electron microscopy (cryo-TEM) and prokaryotic split Venus complementation assays. Lactulose and melibiose further reduced α-synuclein aggregation and associated oxidative stress, as well as protected cells against α-synuclein-induced neurotoxicity by up-regulating autophagy and nuclear factor, erythroid 2 like 2 (NRF2) pathway in DAergic neurons derived from SH-SY5Y cells over-expressing α-synuclein. Our findings strongly indicate the potential of lactulose and melibiose for mitigating PD neurodegeneration, offering new drug candidates for PD treatment.